2020
DOI: 10.1007/s11548-020-02263-3
|View full text |Cite
|
Sign up to set email alerts
|

Value of the surgeon’s sightline on hologram registration and targeting in mixed reality

Abstract: Purpose Mixed reality (MR) is being evaluated as a visual tool for surgical navigation. Current literature presents unclear results on intraoperative accuracy using the Microsoft HoloLens 1®. This study aims to assess the impact of the surgeon’s sightline in an inside-out marker-based MR navigation system for open surgery. Methods Surgeons at Akershus University Hospital tested this system. A custom-made phantom was used, containing 18 wire target crosses within its inner walls. A CT scan was obtained in ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…The main advantage of such markers is that camera pose can be obtained with only one marker usage [13]. Moreover, binary square fiducial markers are widely used in medical research and practice, as they are simple, highly reliable, and multifunctional solution [14][15][16].…”
Section: Methodsmentioning
confidence: 99%
“…The main advantage of such markers is that camera pose can be obtained with only one marker usage [13]. Moreover, binary square fiducial markers are widely used in medical research and practice, as they are simple, highly reliable, and multifunctional solution [14][15][16].…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the method and quality of the registration, the user’s viewing angle and the quality of the AR visualization can affect AR-guided performance. The importance of viewing angle was demonstrated by a study that found that strictly perpendicular sightlines resulted in better accuracy than free sightlines when guiding a needle tip to a target with 3D-AR guidance [58] . Another important factor in 3D-AR visualization is the user’s inter-pupillary distance (IPD).…”
Section: Other Factors Affecting Accuracymentioning
confidence: 99%
“…Mixed reality (MR) technology is a new digital holographic imaging technology that emerged after virtual reality (VR) and augmented reality (AR) (Barteit et al, 2021), which combines a realistic physical model with a pre‐constructed virtual image for its display (Dennler et al, 2020; Wang et al, 2020). This allows the wearer to “see through the eyes” of a surgeon while feeling a physical model (Wang et al, 2019), thus assisting students to learn relevant procedures (Luzon et al, 2020). The purpose of this study is to investigate whether MR technology‐assisted teaching can improve the effectiveness of teaching posterior medial spinal nerve blocks and to investigate students' attitudes toward this new approach.…”
Section: Introductionmentioning
confidence: 99%
“…The high cost of MR devices is not conducive to the budget of some hospitals and schools. The navigation effect and accuracy of MR devices in clinical practice are influenced by the patient's breathing, body shape, and tissue deformation, which can easily lead to errors in punctures (Luzon et al, 2020).…”
mentioning
confidence: 99%